The Effect of Red Bean Extract (Phaseoulus Vulgaris L. Sp.) on T Helper 17, T Regulator Levels, and Atretic Follicle Count in Mice Models of Premature Ovarian Failure Induced by Systemic Lupus Erythematosus - Effendi, Madina Paramitha; Noryanto, Mukhamad; Wiyasa, I Wayan Arsana; Arianto, Onni Dwi (Asian Journal of Health Research, 2025)
Introduction: Systemic Lupus Erythematosus (SLE) is a long-term autoimmune disease that primarily impacts women of reproductive age. A major complication of SLE treatment with cyclophosphamide is premature ovarian failure (POF), leading to infertility. The imbalance between T-helper 17 (Th-17) and T-regulator (Treg) cells contributes to SLE progression. Red bean extract (Phaseolus vulgaris L. sp.), known for its antioxidant and anti-inflammatory effects, may help restore this balance and protect ovarian function. Material and Methods: Female Balb/c mice were divided into five groups: control, untreated SLE, and three treatment groups receiving red bean extract at 50, 75, and 100 mg/kg. SLE was induced using pristane, followed by cyclophosphamide to trigger POF. The treatment groups received red bean extract for four weeks. Th-17 and Treg levels were measured using ELISA, and ovarian tissues were histologically analyzed to assess atretic follicle count. Data were statistically analyzed using ANOVA and Tukey’s post hoc test. Results: Red bean extract reduced Th-17 levels and increased Treg levels, indicating improved immune balance. Additionally, a decrease in atretic follicles suggested protective effects on ovarian function. The most significant results were observed at the 75 mg/kg dose. The extract’s polyphenolic and phytoestrogenic content likely contributed to its anti-inflammatory and antioxidant activity. Conclusion: Red bean extract shows promise as a natural therapeutic agent for preventing ovarian dysfunction in SLE-induced POF by modulating immune response and reducing follicular damage. Further research is needed to explore its molecular mechanisms and clinical potential in humans.